Utilization of Computer Aided Design Software as a Visual Simulation - Ramadhan, Ali; Atmadi, Tunjung; Dinata, Rizki (International Humanities and Applied Science Journal, 2019)
Software is known as one of the components found on a computer. As a software, computer-aided design can be used as a tool to realize ideas. In the process, to be able to realize the idea, it is necessary to have a visual simulation as an aid to be able to see conditions that are able to represent the results of the ideas made. By using qualitative descriptive methods. this research will be useful to be able to provide information to users of computer-aided design software as a basis for using software to produce visual simulations Computer-aided design software in its development can help users to be able to see the condition of a design in a form that represents the original shape. and also can minimize the use of real prototypes to deliver design results. Keywords: Devices, Software, computer-aided design, Simulation, Visual.